2009
DOI: 10.1128/aac.01178-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Posaconazole Administered Orally or by Nasogastric Tube in Healthy Volunteers

Abstract: The use of a nasogastric tube is one means of administering antifungal therapy to critically ill patients unable to receive medication via the oral route. This was a phase 1, open-label, single-center, randomized, crossover study of posaconazole administered via nasogastric tube in healthy volunteers. Each subject received two 400-mg single doses of posaconazole, one administered orally and one administered by nasogastric tube, with a 7-day washout period between each dose. Posaconazole was administered 5 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…A study in healthy volunteers demonstrated a 24% reduction in posaconazole area under the plasma concentration-time curve when administered via NG tube (40), with clinical studies in patients also confirming a significant reduction in posaconazole exposure (7,41). The lack of significance of this covariate in the present study is likely due to the small number of patients who received posaconazole via NG tube in this analysis (n ϭ 8).…”
Section: Discussioncontrasting
confidence: 53%
“…A study in healthy volunteers demonstrated a 24% reduction in posaconazole area under the plasma concentration-time curve when administered via NG tube (40), with clinical studies in patients also confirming a significant reduction in posaconazole exposure (7,41). The lack of significance of this covariate in the present study is likely due to the small number of patients who received posaconazole via NG tube in this analysis (n ϭ 8).…”
Section: Discussioncontrasting
confidence: 53%
“…In Fig. 1 33. The widest ranges were seen for FLC (range, 1 to Ն64 g/ml) and 5FC (range, 0.5 to 64 g/ml).…”
Section: Resultsmentioning
confidence: 96%
“…The triazole POS is an expanded-spectrum triazole with fungicidal activity against a wide spectrum of molds, including Aspergillus species and members of the Mucorales, as well as enhanced activity against Candida and other yeasts (33). The echinocandins represent the newest class of antifungals that exhibit fungicidal activity against many Candida species, making this drug class a desirable alternative to the azole agents, which exhibit only static activity against yeasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS, not significant. ) and AUC values that were only 80% of those observed after oral administration (6). Third, lung transplantation is increasingly offered to older patients.…”
mentioning
confidence: 99%